2011
DOI: 10.1631/jzus.b1100039
|View full text |Cite
|
Sign up to set email alerts
|

Red pigment production by Penicillium purpurogenum GH2 is influenced by pH and temperature

Abstract: Abstract:The combined effects of pH and temperature on red pigment production and fungal morphology were evaluated in a submerged culture of Penicillium purpurogenum GH2, using Czapek-Dox media with D-xylose as a carbon source. An experimental design with a factorial fix was used: three pH values (5, 7, and 9) and two temperature levels (24 and 34 °C) were evaluated. The highest production of red pigment (2.46 g/L) was reached with a pH value of 5 and a temperature of 24 °C. Biomass and red pigment production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
62
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(73 citation statements)
references
References 22 publications
9
62
0
2
Order By: Relevance
“…These pigments are frequently more stable and soluble than pigments from plant or animal sources; in addition, they may present high productivity and are used as additives, color intensifiers, antioxidants, etc. (Méndez et al, 2011). This species was also detected in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…These pigments are frequently more stable and soluble than pigments from plant or animal sources; in addition, they may present high productivity and are used as additives, color intensifiers, antioxidants, etc. (Méndez et al, 2011). This species was also detected in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…Also, pH can affect enzyme activity involved in biosynthesis of pigments (Pisareva et al 2005). Optimum red pigment production by P. purpurogenum GH2 was observed at 24°C and pH 5 in CD medium with no relation between pigment and biomass production (Mendez et al 2011). Afshari et al (2015) reported that Penicillium aculeatum ATCC 1049 produces yellow pigment at 30°C and pH 6.5 while the biomass (11.12 g/L) production was found to be maximum at 30°C and pH 8.…”
Section: Discussionmentioning
confidence: 99%
“…Following removal of alcohol, the colorant is obtained in the crystalline form as a dark red powder. In strains of Penicillium purpurogenum 93 , a red pigment of HAQN-type (none completely characterized) was also observed.…”
Section: Hydroxyanthraquinoid Pigments From Fungimentioning
confidence: 99%
“…Some strains of Aspergillus (A. glaucus, A. cristatus and A. repens) 4,5,35,36,[92][93][94] were found to produce known yellow and red HAQN compounds such as emodin (yellow, group A 1 ), physcion (yellow, group A 1 ), questin (yellow to orange-brown, group A 2 ), erythroglaucin (red, group A 1 ), catenarin (red, group C 1 ; see Table 3) and rubrocristin (red, group C 1 ; see Table 3). However, by using Penicillium or Aspergillus strains, …”
Section: Hydroxyanthraquinoid Pigments From Fungimentioning
confidence: 99%